Pumilacidin-Like Lipopeptides Derived from Marine Bacterium Bacillus sp. Strain 176 Suppress the Motility of Vibrio alginolyticus - Xiu, Pengyuan (Appl Environ Microbiol, 2017)
Bacterial motility is a crucial factor during the invasion and colonization processes of pathogens, which makes it an attractive therapeutic drug target. Here, we isolated a marine bacterium (Vibrio alginolyticus strain 178) from a seamount in the tropical West Pacific that exhibits vigorous motility on agar plates and severe pathogenicity to zebrafish. We found that V. alginolyticus 178 motility was significantly suppressed by another marine bacterium, Bacillus sp. strain 176, isolated from the same niche. We isolated, purified, and characterized two different cyclic lipopeptides (CLPs) from Bacillus sp. 176 using high-performance liquid chromatography, mass spectrometry, and nuclear magnetic resonance spectroscopy. The two related CLPs have a pumilacidin-like structure and were both effective inhibitors of V. alginolyticus 178 motility. The CLPs differ by only one methylene group in their fatty acid chains. In addition to motility suppression, the CLPs also induced cell aggregation in the medium and reduced adherence of V. alginolyticus 178 to glass substrates. Notably, upon CLP treatment, the expression levels of two V. alginolyticus flagellar assembly genes (flgA and flgP) dropped dramatically. Moreover, the CLPs inhibited biofilm formation in several other strains of pathogenic bacteria without inducing cell death. This study indicates that CLPs from Bacillus sp. 176 show promise as antimicrobial lead compounds targeting bacterial motility and biofilm formation with a low potential for eliciting antibiotic resistance. IMPORTANCE Pathogenic bacteria often require motility to establish infections and subsequently spread within host organisms. Thus, motility is an attractive therapeutic target for the development of novel antibiotics. We found that cyclic lipopeptides (CLPs) produced by marine bacterium Bacillus sp. strain 176 dramatically suppress the motility of the pathogenic bacterium Vibrio alginolyticus strain 178, reduce biofilm formation, and promote cellular aggregation without inducing cell death. These findings suggest that CLPs hold great promise as potential drug candidates targeting bacterial motility and biofilm formation with a low overall potential for triggering antibiotic resistance.